Lygaeoidea (Hemiptera: Heteroptera) from National Natural Parks (NNP) with new records of Colombia - RENGIFO-CORREA, LAURA ALEXANDRA; GONZÁLEZ-OBANDO, RANULFO (Revista Colombiana de Entomología, 2011)
Lygaeoidea is one of the largest groups of the suborder Heteroptera but, due to their diversity, there are not taxonomic reviews of the group in Colombia. Taxonomic information is needed as a base line to allow other kind of studies, including those aimed at conservation. for improve understanding about this taxon, a list of the genera of Lygaeoidea Natural Parks of Colombia is provided. 19 genera of Lygaeoidea that belong to six families are listed. Craspeduchus xanthostaurus, Epipolops scudderi, Jalysus reductus, Melanopleurus inflatus, Neoninus sp., Ninyas sp., Ochrostomus brasiliensis, Polychisme poecilus and Spilostethus pandurus are new records to Colombia. Spilostethus pandurus is also recorded for first time in the Neotropic. Diagnosis, photographs for each genera and collecting places in the National Parks are provided.